2013
DOI: 10.1186/1741-7015-11-110
|View full text |Cite
|
Sign up to set email alerts
|

Physical comorbidities in men with mood and anxiety disorders: a population-based study

Abstract: BackgroundThe mind-body nexus has been a topic of growing interest. Further data are however required to understand the specific relationship between mood and anxiety disorders and individual physical health conditions, and to verify whether these psychiatric disorders are linked to overall medical burden.MethodsThis study examined data collected from 942 men, 20 to 97 years old, participating in the Geelong Osteoporosis Study. A lifetime history of mood and anxiety disorders was identified using the Structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 75 publications
3
32
0
Order By: Relevance
“…Some human studies also suggested a relationship between anxiety disorders and thyroid abnormalities [33,36]. In the present study, we found lower T3 levels in CHF animals, whereas serum TSH and T4 levels remained unchanged in these animals.…”
Section: Oxygen Consumptionsupporting
confidence: 69%
“…Some human studies also suggested a relationship between anxiety disorders and thyroid abnormalities [33,36]. In the present study, we found lower T3 levels in CHF animals, whereas serum TSH and T4 levels remained unchanged in these animals.…”
Section: Oxygen Consumptionsupporting
confidence: 69%
“…It is common that people do not seek professional help for mental health problems 34. Untreated mental disorders can manifest as unexplained physical symptoms such as headache or back pain, or they are risk factors for somatic diseases (eg, thyroid diseases or diseases of the digestive system) 46 47. Thus, it is important to pay attention to mental and somatic diseases of Chernobyl cleanup workers simultaneously.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, these anxiety and related disorders occur frequently with a range of general medical disorders [4,5], including gastrointestinal disease [6], pulmonary disease [7, 8], cardiovascular disease [9], endocrine disorders [10], dermatological disorders [11] and cancer [12], as well as neuropsychiatric disorders such as chronic pain [13, 14], migraines [15], dementia [16] and Parkinson's disease [17]. In this chapter we review the epidemiology of comorbid anxiety and related disorders and physical illness, the growing evidence of a bidirectional relationship between these sets of conditions [18] and relevant randomized controlled trials in this area.…”
Section: © 2015 S Karger Ag Baselmentioning
confidence: 99%